Improving home care: Knowledge creation through engagement and design - Groop, Johaan; Gupta, Mahesh; Holmström, Jan; Ketokivi, Mikko (Elsevier B.V., 2017)
In this paper,we apply a design science approach to help a Northern European city improve the efficiency of its home care delivery system. Our proposed solution emerges as a synthesis of applying Goldratt's Theory of Constraints and the principles of variable-demand inventory replenishment. The improved system exhibits both more level resource utilization and higher productivity due to more efficient capacity utilization. In addition to improving system efficiency,we gain insights into how authentic operations management problems can be addressed through design research. A crucial aspect of empirically-rooted practical problems is that they always involve multiple stakeholders with only partially overlapping preferences. Consequently,one must not assume or ascribe an a priori system objective,instead,it must arise from explicit empirical analysis of the relevant stakeholders. Another characteristic of authentic problems is that they are always embedded in an institutional context that sets significant boundary conditions to the feasibility of solutions. These boundary conditions are an important reminder of the complexity of empirically-rooted managerial problems. © 2017
Keywords: Design; Efficiency; Home health care; Problem solving; Delivery systems; Design science; European cities; Home care; Inventory replenishment; Knowledge creations; Practical problems; Problem-solving; Theory of constraint; Variable demands; Boundary conditions; Design science; Health care; Home care; Practical problems; Problem solving; Theory of Constraints; ODS 8 - Trabajo decente y crecimiento económico; ODS 9 - Industria, innovación e infraestructura